MEMAJUKAN POTENSI EKONOMI MASYARAKAT DESA RANTAU MAKMUR MELALUI PROGRAM PELATIHAN PEMBUATAN BAKSO - Ghazali, Ahmad; Muhammad Dwipa Yumna; Salma, Salma; Buti, Nur Aini; Jumiati, Juniati; Ardaniah, Ulil; Rhamadani, Riqfa Aulia; M, Miftakhul Rizal; Iswanto, Iswanto (P3M STAI Sangatta, 2024)
This study aims to strengthen household scale economic businesses in Rantau Makmur Village through training in making meatballs. In the context of village life, household scale businesses have great potential to empower communities and improve the local economy. The method used is step by step training regarding making meatballs. This training includes an introduction to raw materials, processing techniques, production processes, packaging and hygiene management. Training participants include housewives and village community members who have an interest in culinary business. The study results showed that the meatball making training was successful in increasing participants' knowledge and skills in processing and packaging products with good hygiene standards. Apart from that, they are also trained in simple financial management and product marketing. The impact of this training is the creation of various household scale micro businesses that produce quality meatballs as a result of the training.